THE EFFECT OF IMMUNOSTIMULANTS FROM NATURAL INGREDIENTS ON VANAMEI SHRIMP (LITOPENAEUS VANNAMEI) IN INCREASING NON-SPECIFIC IMMUNITY TO FIGHT DISEASE - Nuri Muahiddah; Rangga Idris Affandi; Wastu Ayu Diamahesa (Aquaculture Department, University of Mataram, 2022)
Vanamei shrimp Litopeneus vannamei is a commodity with high economic value. Shrimp is Indonesia's main export commodity. The high value of sales and production of vanamei shrimp is constrained by the many disease attacks in the vanamei shrimp farming industry. An alternative solution that has been continuously researched for several years to combat shrimp disease is using immunostimulants from natural ingredients. Using natural ingredients for immunostimulants can increase the non-specific immunity of vanamei shrimp to ward off disease and be environmentally friendly. Immunostimulants can be administered orally, by immersion, or by injection. Immunostimulants from natural ingredients such as spirulina platensis, polysaccharides from seaweed such as carrageenan, sodium alginate, and fucoidan, extracts from red seaweed, as well as the use of polysaccharides from the bacterium Nodulisporium sp. KT29, Trichoderma sp. able to increase the non-specific immune system in L. vannamei shrimp. These immunostimulants increase non-specific immunity, such as total hemocyte count, phagocytosis activity, phenoloxidase, phagocytic, respiratory burst, superoxide dismutase, and total plasma protein. Immunostimulants from these natural ingredients can also fight infectious disease attacks.